The importance of using the oral glucose tolerance test when assessing the glycemic profile in patients with adrenal incidentaloma - Magarão Costa, Julia; Rebelo, João Felipe Dickson; Perozo, Andrea Faria Dutra Fragoso; Junqueira, Fernanda Damasceno; De Almeida, Ana Beatriz Alcantara Bérenger Samarcos; Milaresco, Juliana Saldanha; Souza, Michele dos Santos; Moraes, Aline Barbosa; Dantas, Joana Rodrigues; Vieira Neto, Leonardo (Frontiers in Clinical Diabetes and Healthcare, 2025)
IntroductionThere are limited data regarding the role of oral glucose tolerance test (OGTT) in classifying glycemic alterations in patients with adrenal incidentaloma (AI). This study aims to compare the frequency of dysglycemia [pre-diabetes mellitus (DM) and DM] among patients with non-functioning adrenal incidentalomas (NFAI), mild autonomous cortisol secretion (MACS), and controls; and to assess the area under the curve (AUC) in the OGTT and determine whether the OGTT was decisive in diagnosing dysglycemia in each population.MethodsA cross-sectional study was conducted on 65 NFAI (1mg-dexamethasone suppression test [DST] ≤1.8μg/dL), 45 MACS (1mg-DST ≥1.9μg/dL), and 56 controls. The control group was selected based on normal adrenal imaging. Patients were classified as normoglycemic or dysglycemic based on fasting glucose, glycated hemoglobin, and OGTT.ResultsAUC >290mg.h/dL was found in 75% of MACS, 55% of NFAI, and 22% of controls (p=0.008). The presence of AI was determinant for this result. Glucose levels ≥155 mg/dL at the 1-hour during the OGTT were observed in 75% of MACS, 65% of NFAI, and 28% of controls (p=0.01). Dysglycemia frequency was higher in MACS and NFAI than controls (91.1 vs. 90.8 vs. 73.2%; p=0.01). The OGTT changed the classification in 27% of MACS, 23% of NFAI, and 3% of controls (p=0.03). Presence of AI increased the odds ratio for benefiting from OGTT to obtain a more accurate dysglycemia classification by 9.5 times.ConclusionPatients with AI had a higher dysglycemia frequency, and a significant number of these patients benefited from OGTT in classifying glycemic alterations.